B7‐H3 promotes nasopharyngeal carcinoma progression by regulating CD8+ T cell exhaustion - Zhaoen Ma; Gui Chen; Hao Li; Saixuan Yang; Yali Xu; Bolin Pan; Wuping Lai; Guangui Chen; Wenjing Liao; Xiaowen Zhang (Immunity, Inflammation and Disease)
Abstract Background B7‐H3 protein is an important regulator of the adaptive immune response in human tumorigenesis. 4‐1BB is a co‐stimulatory receptor expressed on activated CD8+ T cells, and regulates T cell immunity. Here, we investigated the role of B7‐H3 in the growth and invasion of nasopharyngeal carcinoma (NPC) and the effect of its interaction with 4‐1BB on tumor immunity. Methods Short hairpin (sh) RNA was designed to knock down B7‐H3 expression in NPC cells. NPC cells with stable knockdown of B7‐H3 were established and injected into nude mice. The effects of B7‐H3 on cell proliferation, apoptosis, and epithelial‐to‐mesenchymal transition (EMT) were detected by the CCK8 assay, flow cytometry, TUNEL assay, and western blot analysis. The migration and invasion abilities were determined using the Transwell assay and scratch assay. Co‐immunoprecipitation (Co‐IP) assays were performed to study the interaction between B7‐H3 and 4‐1BB. Anti‐4‐1BB antibody was used in a co‐culture system and xenograft mice to study the effect of 4‐1BB on NPC development. Results NPC cells transfected with sh‐B7‐H3 showed a higher rate of apoptosis, slower growth rate, impaired migration, and less EMT in vitro. Xenograft mice with stable knockout of B7‐H3 had lower tumor burdens, and the stripped tumors had lower rates of cell proliferation, higher rates of apoptosis, and less EMT in vivo. Additionally, decreased B7‐H3 expression was positively correlated with interferon‐γ, tumor necrosis factor‐α, and 4‐1BB+CD8+ tumor‐infiltrating lymphocytes. Co‐IP studies showed that B7‐H3 interacts with 4‐1BB. Also, the inhibitory effects of sh‐B7‐H3 on NPC tumor growth, invasion, and tumor immunity could be alleviated by the anti‐4‐1BB antibody both in vivo and in vitro. Conclusion Our findings suggest that B7‐H3 may accelerate tumor growth, tumor cell invasion, and EMT, and interact with 4‐1BB to produce CD8+ T cell exhaustion that inhibits tumor immunity. B7‐H3 might serve as a novel target for treating NPC.